Mediatisasi Hadis: Studi Analisis Hadis Bentuk Video Era New Media - Wijayanti, Sherina; Muhammad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2023)
This article captures the variety of presenting hadiths in the form of videos and the functions of the generated content, both from a religious and economic perspective. The research method employed by the author is qualitative, involving direct observation of hadith video content on Facebook, Instagram, TikTok, and YouTube. This study focuses on videos that use hadith as content material on social media. The questions raised are how does the media influence the study of hadith in the new media era? Is there a shift in the function of hadith when hadith is packaged in the form of videos and disseminated through social media? The research findings indicate that media has provided an open opportunity for users to disseminate hadiths based on their understanding, granting people the freedom to think without limits when receiving presented hadith content. In the era of new media, hadiths are not only utilized for religious expression but have also entered the realm of economic functions. Nevertheless, the content of hadiths shared on social media often lacks in transforming the text into a more simplified form, leading to a reduction in religious understanding.